Breaking through unravel problems in ERP implementation using agile - Fernandi Wijaya, Santo; Ervina Jeanette Egeten, Angelina (Journal of Advanced Computer Science & Technology, 2019)
Demand for the industry to enhance competitive advantage. For that, the industry is required to make a breaking through in order to enhance the organizational performance. This is a reason for addressing the inefficiencies in managing people, processes, organizations, and technology. One of the efforts in improving organization performance is the development in the field of Information Systems as an effort to improve the agility of the organization. ERP system is one solution that can be employed in order to improve organization performance. However, in reality, industrial companies face problems in ERP implementation. This is a challenge to solve the problems of implementing an ERP system for industry. In this opportunity, researchers intend to conduct a re-search to identify the problems of factors in the ERP implementation, namely by proposing agile methods as one of the new methodologies in the effort to solve the problems in the ERP implementation for an industry. The results of this study will result in an agile model of implementing ERP for improving the capacity of ERP systems. This study idea is to analyze the agile method as a solution alternative to make changes for the ERP implementation success. This study is using Structural Equation Modeling as a quantitative data analysis approach of an industry as a case study.Â Â Â